Stroke-like lesion and status epilepticus in a child with NARS2-related combined oxidative phosphorylation deficiency 24 - Su, Song; Hu, Wandong; Liu, Yong; Lang, Qiong; Zhang, Hongwei (Frontiers in Neurology, 2025)
IntroductionThe NARS2 gene encodes mitochondrial asparaginyl-tRNA synthetase, and biallelic pathogenic variants have been associated with combined oxidative phosphorylation deficiency 24 (COXPD24), an autosomal recessive mitochondrial disorder characterized by highly heterogeneous clinical manifestations. This study retrospectively analyzed the clinical and genetic findings of a Chinese infant presenting with status epilepticus and explored potential genotype–phenotype correlations.MethodsClinical data, laboratory tests, neuroimaging, and disease course of the proband were reviewed. Whole-exome sequencing (WES) and copy-number variation (CNV) analysis were performed to identify causative variants in NARS2. Candidate variants were assessed by population database screening and literature review.ResultsThe proband, a 9-month-old girl, presented with status epilepticus, global developmental delay, increased muscle tone, elevated serum lactate and myocardial enzyme levels. Brain magnetic resonance imaging (MRI) revealed a focal cerebral lesion consistent with a metabolic or stroke-like infarction, as well as delayed myelination. WES identified compound heterozygous NARS2 variants: a large exon 6–11 deletion and a novel missense variant c.467T>C (p.Leu156Ser), inherited in an autosomal recessive manner. Both variants were absent from public population databases and published literature. Notably, cerebral infarction has not been previously reported in NARS2-related disorders, suggesting a potential expansion of the clinical spectrum.DiscussionReview of previously reported NARS2 variants indicates that both missense and loss-of-function mutations can lead to variable disease severity depending on residual enzyme activity. This case broadens the phenotypic and mutational spectrum of NARS2-associated COXPD24 and highlights the importance of evaluating large exon deletions and novel variants in infants with early-onset mitochondrial encephalopathy and epileptic manifestations.